Revenue Generation and Local Government autonomy issues in Anambra State - Fidelia Ifeyinwa Nzekwe-Chinwuko (Siber Nusantara Research, 2025)
Local governments in Nigeria are often described as the closest tier to the people, yet many of them struggle to meet even basic developmental expectations. In Anambra State, this struggle is shaped largely by how revenue is raised, who controls it, and how much freedom councils actually have to make financial decisions. The study used a descriptive survey design to examine revenue generation across six local governments in Anambra State, covering Awka North, Idemili North, Aguata, Nnewi North, Anambra East, and Onitsha North. A projected population of 1,919,000 served as the study population. Using the Taro Yamane formula at a 5 percent margin of error, a sample size of 400 was determined and proportionally distributed across the LGAs. Data were collected through a validated and reliable structured questionnaire, supported by secondary sources. Analysis employed descriptive statistics and multiple regression using SPSS 20 at a 5 percent significance level to test hypotheses and identify revenue generation patterns. The gender distribution showed more female respondents [210; 58 percent] than males [153; 42 percent]. Analysis of five infrastructure indicators revealed generally low implementation levels. Palliatives on feeder roads scored low extent [33.5 percent], agro-allied implements also low [24.9 percent], and borehole water moderate [40.3 percent]. Primary healthcare outreach recorded moderate extent [28.4 percent], while environmental sanitation showed very low extent [42.5 percent]. Respondents rated infrastructure provision as low [46.16 percent], moderate [20.54 percent], and high [33.30 percent]. Hypothesis testing showed a significant negative relationship between lack of autonomy and infrastructure provision [t=1.628; p=0.002], leading to rejection of the null hypothesis. The study concludes that strengthening local government autonomy is not merely a reform proposal; it is essential for improving revenue performance and enabling more responsive, development-oriented administration at the grassroots.